Eksistensi Dan Transformasi Petani Gurem: Kasus Pertanian Wilayah Pinggiran Kota Bandung - Yonas Hangga Saputra (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
This article aims at: (1) describing the existence and transformation of small-scale farmers; (2) identifying the problems of small-scale farmers related to the land tenure pattern, farming system, and institutional aspect; and (3) recommending the policy for small-scale farmers empowerment, case of sub-urban area of Bandung municipality.  The  research  results  show  that  the  existence  and  transformation  of small-scale farmers were degraded. The most problem faced by small-scale farmers in locale of the study was agricultural land conversion to non-agricultural purposes. Consequently, the proportion of small-scale farmers who operate their owned land was decreased and some of them transformed to the status of cultivated farmers either in rented or shared systems or became farm laborers. Moreover, the farm productivity was not optimal while the position of small-scale farmers especially the cultivated farmers became feeble in negotiation with owned land as well as in terms of capital aspect. The empowerment program intervention should be followed by technical assistance in line with aspiration of small-scale farmers toward collectively participatory in the organization of farmers. It should be implemented through participatory young generation both in on-farm and in off-farm activities.